Business Strategy Formulation Using Business Model Case Study: PT. Kartina Tri Satria - Priandita, Audria; Toha, Mohamad (The Indonesian Journal of Business Administration, 2013)
Muslim fashion in Indonesia is rapidly growing. Until a few decades ago the Islamic fashion is not particularly common in Indonesia, but recently has become a trend, not only among those wearing them, but also as a production sector. PT. Kartina Tri Satria is one of the companies that are in the competition of products or brand fashions which going on at the moment. PT. Kartina can perform some steps to strengthening the quality of the product and to providing excellent service to their customers.Â Keywords: Textile Industry, PT. Kartina Tri Satria, Muslim Wear, Business Strategy, Business Model Canvas.